Comparative Analysis of Arabic-Indonesian and Arabic-English Translation Techniques in The Al-Hikam Aphorism - Muhammad Yunus Anis; Arifuddin Arifuddin (JURNAL ARBITRER, 2023)
This study examines the translation techniques used in the Arabic, Indonesian, and English languages. One of the studies in textual equivalence involves the translation of the information structure of Themes (starting point of speech) and Rheme (new information). Mapping the structure of the Themes and Rheme in the source language text (SL) will assist the translator in determining the flow of information and identifying the type of genre in both the source and the target text. Thus, the research problems can be stated as follows: (1) what the form of information structure is in Al-Hikam aphorisms, and (2) how to apply translation techniques in Al-Hikam aphorisms. The results show that Arabic-to-Indonesian and Arabic-to-English aphorism translations employ a variety of translation techniques. There are 1,169 different translation techniques utilised in Al-Hikam aphorisms (Arabic to Indonesian). Meanwhile, the number of translation techniques in Al-Hikam aphorisms (Arabic – English) amount to 962. On the other hand, the dominance of established equivalent techniques in Arabic – Indonesian and Arabic – English translations indicates that there are many terms or expressions that have been recognised in the dictionary or are commonly used to achieve equivalence from the source language to the target language, thereby increasing the readability of aphorism. The results of macro level data analysis indicate that translation of Al-Hikam’s aphorisms in Arabic - Indonesian and Arabic - English tends to be oriented towards the target language and adopts the ideology of domestication.